Development of longitudinal flight simulator - He, Yufan (Nanyang Technological University, 2022)
In this report, the construction and testing an open-loop longitudinal flight simulator are discussed. The core simulation engine is built in Simulink and the input are attitudes of the aircraft model in wind tunnel and the forces experienced by the aircraft model in inertial frame of reference. Integrating process between the Simulink model, the sensors used to obtain airplane model status and the actuators in the airplane model are covered. Two different aircraft models are developed to test the simulator. First model is modified from a glider bought off-the-shelf, additional control surface are added to make it fully actuated and the model is fixed on top of the force sensor by a rod and a spherical bearing so that the translational motions are constrained while rotation is free in 3 DoF (pitch, roll, and yaw). Second model is build using wood rod as fuselage and NACA 2412 as the airfoil of a foam wing. The motion of the model is restricted to pitch only by a ball bearing attached at the CG location of the plane. And elevator in the tail is the only one control surface created for the model. Limitation of the simulator is discovered through simulation experiment using first model, the horizontal forces transferred through a rod is not accurate and the flow condition required by the simulator cannot be satisfied. In the simulation of second model, only longitudinal motions are simulated and a method to synchronize the control and simulation results is discussed. XFLR analysis for the aircraft model is carried out to obtain the drag and lift produced in the simulated environment. Elevator control for maneuvers such as controlled climbing and climbing and descending to the same level is loaded to an Arduino Mega which act as controller of the aircraft and the control is implemented during simulation. The simulated trajectory fits the intended trajectory, and the simulation results also reflects some of the aerodynamic characteristics. Future work that can be done to improve the simulator is also discussed.